Study contamination of lead, cadmium and mercury in coastal water along Kelantan Coast - Mariam Firdhaus Mad Nordin; Marinah Muhammad (2011)
Samplea of coastal water ware collected from five sampling station along Kelantan coast base on Department of Environment (DOE) requirement. Sample randomly collected every year since year 1996 until now by DOE, at Sri Tujoh Beach, Sabak Beach, Cahaya Bulan Beach, Irama Beach and Bisikan Bayu Beach on situation and environmental condition. Heavy metals which are Lead (Pb), Cadmium (Cd) ansd Mercury (Hg) ware determine using Standard for Examination of Water and Wastewater. The samples preserved and digested using nitric acid (HNO3) and hydrochloric acid (HC1) before analyzing using Flame Atomic Absorption (AA) and other method Cold Vapor Atomic (CVAA) required for determination of Hg.Selection of method depend on level of heavy metal concentration present in water sample which AA used to determination high level of heavy metal, and CVAA use to determine low level of heavy metal. Digestion using HNO3 and HC1 required to remove organic and solubilized solid matter by oxidation and volatilization. The results obtain were compared with Interim Marine Water Quality cannot qualify as save level because it higher than IMWQS limits.